Toward a Gender-Responsive Translation of the Qur’an: A Study of the Revised Al-Qur’an dan Terjemahnja by the Indonesian Ministry of Religious Affairs - Faizin, Hamam; Fauzan; Krisnawati, Nofi Maria (KALAM, 2025)
Al-Qur’an dan Terjemahnja, published by the Indonesian Ministry of Religious Affairs (MoRA), has often been criticized by scholars for reflecting gender-biased interpretations. However, the revisions conducted between 1998 and 2002 indicate attempts to address gender-related concerns in the Indonesian translation of the Qur’an. This article examines how gender discourse influenced the revision of the translation during the Reformasi period. Using a qualitative descriptive approach and Roger Fowler’s critical discourse analysis, this study analyzes linguistic changes introduced in the revised edition of Al-Qur’an dan Terjemahnja. The analysis shows that several translation choices were modified to reflect a more gender-responsive perspective. For instance, the term wanita was replaced with perempuan, the description of women’s creation was reformulated, and the term pemimpin (leader) was translated as pelindung (protector). In addition, women were no longer consistently positioned as direct objects of male desire. These revisions indicate a shift from a more patriarchal orientation toward a gender-responsive translation. The study argues that this transformation was closely linked to the expanding gender discourse during the Reformasi era, particularly the institutionalization of gender mainstreaming policies in Indonesia.